Pembuatan Abon Ikan Nila Sebagai Upaya Pemanfaatan Sumber Daya Perairan untuk Meningkatkan Ekonomi Masyarakat di Pekon Kagungan - Pratama, Lekat Dewa; Nazamudin, Ahmad; Hidayat, Fariz Nur; Pranita, Wullan Rhegina; Amelia, Atikah Putri; Ismayanti, Syifa Nur; Putri, Clarissa Salsabila; Widyastuti, RA. Diana (Research and Social Study Institute (RESSI), 2023)
This service is carried out as an effort to provide innovation and increase public awareness in managing and maximizing the potential of tilapia into shredded processed products. Shredded fish is one of the processed products of fishery products from seasoned fish meat. This activity was carried out at the Pekon Kagungan hall on January 29, 2023, which was aimed at housewives in Pekon Kagungan who are members of the family welfare empowerment group (PKK). This activity was carried out with the method of socialization and direct demonstration to make it easier for the participants who attended to understand the procedures for making shredded. Based on the results of the evaluation after the implementation of the activity, the majority of participants were very enthusiastic in learning the procedures in shredded processing. Participants knew how the process of processing raw tilapia into shredded processed products